Novel approaches to the prediction, diagnosis and treatment of cardiac late effects in survivors of childhood cancer: a multi-centre observational study - Skitch, Amy; Mital, Seema; Mertens, Luc; Liu, Peter; Kantor, Paul; Grosse-Wortmann, Lars; Manlhiot, Cedric; Greenberg, Mark; Nathan, Paul C (Université d'Ottawa | University of Ottawa, 2017)
Abstract Background Anthracycline-induced cardiac toxicity is a cause of significant morbidity and early mortality in survivors of childhood cancer. Current strategies for predicting which children are at greatest risk for toxicity are imperfect and diagnosis of cardiac injury is usually made relatively late in the natural history of the disease. This study aims to identify genomic, biomarker and imaging parameters that can be used as predictors of risk or aid in the early diagnosis of cardiotoxicity. Methods This is a prospective longitudinal cohort study that recruited two cohorts of pediatric cancer patients at six participating centres: (1) an Acute Cohort of children newly diagnosed with cancer prior to starting anthracycline therapy (n = 307); and (2) a Survivor Cohort of long-term survivors of childhood cancer with past exposure to anthracycline (n = 818). The study team consists of three collaborative cores. The Genomics Core is identifying genomic variations in anthracycline metabolism and in myocardial response to injury that predispose children to treatment-related cardiac toxicity. The Biomarker Core is identifying existing and novel biomarkers that allow for early diagnosis and prognosis of anthracycline-induced cardiac toxicity. The ﻿Imaging Core is identifying echocardiographic and cardiac magnetic resonance (CMR) imaging parameters that correspond to early signs of cardiac dysfunction and remodeling and precede global dysfunction and clinical symptoms. The data generated by the cores will be combined to create an integrated risk-prediction model aimed at more accurate identification of children who are most susceptible to anthracycline toxicity. Discussion We aim to identify genomic risk factors that predict risk for anthracycline cardiotoxicity pre-exposure and imaging and biomarkers that facilitate early diagnosis of cardiac injury. This will facilitate a personalized approach to identifying at-risk children with cancer who may benefit from cardio- protective strategies during therapy, and closer surveillance and earlier initiation of medications to preserve heart function after cancer therapy. Trial registration NCT01805778 . Registered 28 February 2013; retrospectively registered.